Dual inhibitors of the dengue and West Nile virus NS2B-NS3 proteases: synthesis, biological evaluation and docking studies of novel peptide-hybrids - Bastos Lima, Allan; Behnam, Mira A. M.; El Sherif, Yasmin; Nitsche, Christoph; Vechi, Sergio; Klein, Christian D. (Bioorganic & medicinal chemistry, 2015)
Dengue virus (DENV) and West Nile virus (WNV) are mosquito-borne arboviruses responsible for causing acute systemic diseases and severe health conditions in humans. The discovery of therapies capable to prevent infections or treat infected individuals remains an important challenge, since no vaccine or specific efficient treatment could be developed so far. In this context, we present herein the synthesis, characterization, biological evaluation and docking studies of novel peptide-hybrids based on 2,4-thiazolidinedione scaffolds containing non-polar groups.